Religiosity as Moderating of Accounting Student Academic Fraud with a Hexagon Theory Approach - Aprillia Kartika Apsari; Dwi Suhartini (Accounting and Finance Studies, 2021)
This study aims to examine and analyze the influence of aspect hexagon theory consisting Pressure, Opportunity, Rationalization, Capability, Arrogance, and Collusion as well as aspect of Religiosity as moderating variable on Academic Fraud. Primary data used in this study were collected using a questionnaires distributed to active students majoring in accounting at UPN “Veteran” East Java of 2017 and 2018 with a total of 106 respondent. The sampling method using simple random sampling technique. The collected data were analyzed using Partial Least Square analysis technique with WarpPLS 7.0 software. The results of this study showed that Pressure and Opportunity do not have a positive and significant effect on academic fraud behavior in accounting student. While Rationalization, Capability, and Collusion have a positive effect on academic fraud and Arrogance do not have a positive effect on academic fraud behavior in accounting student. Religiosity as a moderating variable is able to moderate, to be more precise, to weaken the pressure and opportunity on academic fraud behavior in accounting student. Meanwhile, religiosity is able to moderate, to more precisely strengthen the capability on academic fraud. Religiosity as a moderating variable is not able to moderate Rationalization, Arrogance, and Collusion on academic fraud behavior in accounting student.